Algorithm of medication review in frail older people: Focus on minimizing the use of high-risk medications - Poudel, Arjun; Ballokova, Anna; Hubbard, Ruth E; Gray, Leonard C; Mitchell, Charles A; Nissen, Lisa M; Scott, Ian A (Geriatrics & gerontology international, 2016)
AIM: Frail older people typically suffer several chronic diseases, receive multiple medications and are more likely to be institutionalized in residential aged care facilities. In such patients, optimizing prescribing and avoiding use of high-risk medications might prevent adverse events. The present study aimed to develop a pragmatic, easily applied algorithm for medication review to help clinicians identify and discontinue potentially inappropriate high-risk medications. METHODS: The literature was searched for robust evidence of the association of adverse effects related to potentially inappropriate medications in older patients to identify high-risk medications. Prior research into the cessation of potentially inappropriate medications in older patients in different settings was synthesized into a four-step algorithm for incorporation into clinical assessment protocols for patients, particularly those in residential aged care facilities. RESULTS: The algorithm comprises several steps leading to individualized prescribing recommendations: (i) identify a high-risk medication; (ii) ascertain the current indications for the medication and assess their validity; (iii) assess if the drug is providing ongoing symptomatic benefit; and (iv) consider withdrawing, altering or continuing medications. Decision support resources were developed to complement the algorithm in ensuring a systematic and patient-centered approach to medication discontinuation. These include a comprehensive list of high-risk medications and the reasons for inappropriateness, lists of alternative treatments, and suggested medication withdrawal protocols. CONCLUSIONS: The algorithm captures a range of different clinical scenarios in relation to potentially inappropriate medications, and offers an evidence-based approach to identifying and, if appropriate, discontinuing such medications. Studies are required to evaluate algorithm effects on prescribing decisions and patient outcomes. Geriatr Gerontol Int 2016; 16: 1002-1013.
Keywords: hodnocení rizik; Female; Age Factors; Polypharmacy; ženské pohlaví; medication withdrawal; Drug-Related Side Effects and Adverse Reactions; věkové faktory; lidé; Aged, 80 and over; bezpečnost pacientů; Risk Assessment; Algorithms; nevhodné předepisování; seznam potenciálně nevhodných léčiv; Frail Elderly; Potentially Inappropriate Medication List; nežádoucí účinky léčiv; medication review; algorithm; Male; křehký senior; Aged; residential aged care facilities; algoritmy; polypharmacy; chronická nemoc; Inappropriate Prescribing; senioři nad 80 let; senioři; mužské pohlaví; Chronic Disease; high-risk medications; Patient Safety; Humans